The Implementation of the Self-Help Housing Stimulus Program (BSPS) to Improve Housing Quality and Community Welfare in Retok Village - Wiratmoko, Danar; Wiro, Marsianus (Jurnal Indonesia Sosial Sains, 2025)
The Self-Help Housing Stimulant Assistance Program (BSPS) is a policy of the Indonesian government aimed at improving the quality of decent housing for low-income people through a self-help (swadaya) approach. This study aims to find out how the BSPS program improves the welfare of the community in Retok village. The method used was a descriptive qualitative study with field observation techniques and in-depth interviews with aid recipients, local implementers, and related agencies. The results of the study show that BSPS has a positive impact on improving the quality of houses, the welfare of beneficiaries, and the surrounding community. However, challenges are still found in the technical aspects of implementation and limited funds. Therefore, it is recommended to strengthen coordination between agencies and increase community capacity in the process of building self-help (swadaya) houses.